MELATIH KECERDASAN MATEMATIS LOGIS ANAK MELALUI KEGIATAN FUN COOKING DI SD NU METRO LAMPUNG - Masrurotul Mahmudah; Nur Laili; Muh. Ngali Zainal Makmun (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2021)
This research was motivated by curiosity in terms of developing logical mathematical intelligence in first grade students at SD NU Metro Lampung. This research focused on Fun Cooking activities which aim to develop children's interests and talents. This study uses critical analysis method, so this study is descriptive qualitative analysis to become a learning innovation in students development at mathematical intelligence. From the results of the study, it can be seen that the first grade students at SD NU are very enthusiastic in participating in Fun Cooking activities. Through several processes, stages and explanations conveyed by the teacher, it turns out that the development of children's logical mathematical intelligence, in first grade students is very efficient and it can be seen that children are able to understand various types of staple food ingredients, dosages in making dough, children are able to understand numbers, understand the duration of time to bake cakes, be creative in printing and make innovations on pizza, understand geometric shapes, for example round, square, triangle, and so on. Keywords: Fun Cooking, Mathematical Intelligence, Interests and Talents